2019
DOI: 10.1155/2019/5410657
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-2-Macroglobulin, a Hypochlorite-Regulated Chaperone and Immune System Modulator

Abstract: Alpha-macroglobulins are ancient proteins that include monomeric, dimeric, and tetrameric family members. In humans, and many other mammals, the predominant alpha-macroglobulin is alpha-2-macroglobulin (α2M), a tetrameric protein that is constitutively abundant in biological fluids (e.g., blood plasma, cerebral spinal fluid, synovial fluid, ocular fluid, and interstitial fluid).α2M is best known for its remarkable ability to inhibit a broad spectrum of proteases, but the full gamut of its activities affects di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 98 publications
1
60
0
5
Order By: Relevance
“…We highlight the presence in our analysis of the HSP90AB1, a known chaperone that facilitates the maturation of a wide range of proteins and its attenuation has been related to idiopathic pulmonary fibrosis and cystic fibrosis (Haase and Fitze, 2015;Wang and Ni, 2016). Our analysis also shows a translation decrease in A2M, a plasmatic protein highly expressed in lung and artery that inhibits a broad spectrum of proteases, including trypsin, thrombin, and collagenase (Cater et al, 2019). A recent study confirms our prediction, A2M level in sera from COVID-19 patients is significantly lower than in healthy subjects (Shen et al, 2020).…”
Section: Resultsmentioning
confidence: 64%
“…We highlight the presence in our analysis of the HSP90AB1, a known chaperone that facilitates the maturation of a wide range of proteins and its attenuation has been related to idiopathic pulmonary fibrosis and cystic fibrosis (Haase and Fitze, 2015;Wang and Ni, 2016). Our analysis also shows a translation decrease in A2M, a plasmatic protein highly expressed in lung and artery that inhibits a broad spectrum of proteases, including trypsin, thrombin, and collagenase (Cater et al, 2019). A recent study confirms our prediction, A2M level in sera from COVID-19 patients is significantly lower than in healthy subjects (Shen et al, 2020).…”
Section: Resultsmentioning
confidence: 64%
“…Together with TXNIP, RPS3A and RPS27A, This is a provisional file, not the final typeset article 4 it is involved in the antigen processing and presentation. Moreover, this gene, along with S100A11, HSP90AB1 and also EEF1A1, regulates the exocytosis of granules containing inflammatory mediators in neutrophils (24).In addition, our analysis shows a translation decrease in A2M, a plasmatic protein that inhibits a broad spectrum of proteases, including trypsin, thrombin and collagenase (6). Finally, we highlight the presence in our analysis of the HSP90AB1, a known chaperone that facilitates the maturation of a wide range of proteins and its attenuation has been related to idiopathic pulmonary fibrosis and cystic fibrosis (16,43).…”
Section: Resultsmentioning
confidence: 63%
“…Consistent with our observation, previous reports showed that patients with CF secrete elevated levels of A1AT and other antiproteases [ 6 ]. Another antiprotease with a significant (3.43-fold) increase identified in our study was alpha-2-macroglobulin, which is known for its remarkable ability to inhibit a broad spectrum of antiprotease activities [ 24 ]. By contrast, we observed a decrease in antithrombin III, which is a serine protease inhibitor that regulates the blood coagulation cascade.…”
Section: Discussionmentioning
confidence: 99%
“…Such regulation ensures the building of highly efficient molecular machinery, which can catalyze the transfer of electrons from cytochrome c to molecular oxygen and ultimately to facilitate the aerobic production of ATP [ 30 ]. In our study, we observed a 2.27-fold decrease in the expression of the cytochrome c oxidase subunit 7A1 (COX7A1), a new member of the COX7A gene family, which is a subunit of the COX holoenzyme that is incorporated into the mitochondrial COX complex [ 24 ]. However, the specific mechanism(s) by which mitochondrial metabolism contributes to CF pathophysiology and the involvement of COX7A1 require further elucidation.…”
Section: Discussionmentioning
confidence: 99%